Low-Molecular-Weight Heparin Versus Unfractionated Heparin in the Treatment of Patients with Acute Pulmonary Thromboembolism - Findik, S; Erkan, ML; Selcuk, MB; Albayrak, S; Atici, AG; Doru, F (Karger, 2002)
Background: Low-molecular-weight heparin (LMWH) appears to be as effective as unfractionated heparin (UFH) for both treatment and prophylaxis of deep vein thrombosis (DVT), but limited data are available for its use in acute pulmonary thromboembolism (PTE). Objective: To determine whether enoxaparin, a LMWH, was clinically as efficient and safe as UFH in patients with a diagnosis of acute PTE. Material and Methods: After exclusion of those with massive forms, 59 patients with acute PTE were randomly assigned to either subcutaneous enoxaparin given twice daily (1 mg/kg/dose) or adjusted dose intravenous UFH. Oral anticoagulant treatment was begun on the second day and was given for at least 6 months. We compared the treatment regimens at day 8 and day 90 with respect to a combined end point of major bleeding, recurrent venous thromboembolism (VTE), and death. Results: In the first 8 days of treatment, 1 of 30 patients assigned to receive UFH (3.3%) reached one of the end points (recurrence), as compared with none of 29 patients assigned to enoxaparin. Statistically this difference was not significant (p = 0.508). By day 90, 3 patients assigned to UFH (10%) had symptomatic recurrent VTE, as compared with 1 patient assigned to enoxaparin (3.4%). There was neither major bleeding nor death in the study groups. There was an absolute difference of 6.4 percentage points between the two treatment groups, but the difference was statistically not significant (p = 0.318). Conclusion: Initial subcutaneous treatment with enoxaparin appeared to be as effective and safe as UFH in acute PTE. Copyright (C) 2002 S Karger AG, Basel.
Keywords: Pulmonary Thromboembolism; Unfractionated Heparin; Low-Molecular-Weight Heparin; Enoxaparin